Crop plans based on frequencies of dry and wet spells at Daringibadi block of Kandhamal district - PARDHAN, P C; SENAPATI, P C; SUBUDHI, C R (The Indian Journal of Agricultural Sciences, 2013)
An investigation was conducted during 1996 for agricultural management and planning of Daringbadi block of Kandhamal district which comprised 70% tribal and scheduled caste population. Markov chain model has been applied to know the probability of having different condition, dry and wet pentads (5 consecutive days) and also forward and backward accumulation of rain water suitable for crop production. The analysis showed that 2 short duration crops can be raised in a year, one in rainy season (kharif) and the other in winter season (rabi). A number of cropping systems including intercropping and sequence cropping have been proposed based on the wealth condition of the region.